THE EFFECTIVENESS OF DIGITAL LITERATURE-BASED LEARNING VIDEO ON IMPROVING STUDENT'S DIGITAL LITERATURE SKILL - Arif Rahman Hakim; Ani Widayati; Eka Ary Wibawa; Yolandaru Septiana (Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to determine the effectiveness of learning videos on improving the digital literacy skills of Accounting Education students between control and experimental classes. This research is quasi-experimental research with a quantitative approach. The quasi-experimental type chosen was the design of the control group that was not treated with the same pre-treatment and post-treatment samples. The study was conducted for six months. The population of this study was 310 students of Accounting Education FE UNY (8 classes) with a sample of 81 students (2 classes). The sampling technique used is purposive sampling. Research data collection techniques use questionnaires and documentation. The validity of the instrument is proved by the analysis of exploratory factors, while its reliability is estimated by the Alpha formula. Data analysis techniques use independent sample t test hypothesis test. The results showed that there was a significant difference in video effectiveness in improving students' digital literacy skills between control and experimental classes with a calculation of 2,881 and a Sig. score of 0.005. The experimental class had a higher average score than the control class with a difference of 5,375. This means that the provision of learning video treatment can improve students' digital literacy skills in the experimental group.